Serum 1,5-Anhydroglucitol to Glycated Albumin Ratio Can Help Early Distinguish Fulminant Type 1 Diabetes Mellitus from Newly Onset Type 1A Diabetes Mellitus - Lingwen Ying; Xiaojing Ma; Yun Shen; Jingyi Lu; Wei Lu; Wei Zhu; Yufei Wang; Yuqian Bao; Jian Zhou (Journal of Diabetes Research)
Background. Fulminant type 1 diabetes mellitus (FT1DM) onsets abruptly and usually occurs within 1 week after the onset of hyperglycemic symptoms. Glycated albumin (GA) and 1,5-anhydroglucitol (1,5-AG) are indicators that reflect short-term glucose levels. This study was aimed at investigating whether the 1,5-AG/GA index (AGI) is a suitable indicator for early FT1DM identification. Methods. A total of 226 subjects were enrolled, all with glycated hemoglobin A1c HbA1c<8.7%. FT1DM was diagnosed based on the 2012 Japan Diabetes Society criteria. Results. The AGI level was 0.54 (0.17–1.36) in the whole group. It was lower in FT1DM patients (0.16 [0.10–0.25]). Among the participants whose HbA1c did not exceed 7.0%, the AGI of FT1DM decreased significantly compared to type 1A diabetes (T1ADM) and latent autoimmune diabetes in adults (LADA) patients (0.16 [0.12–0.26] vs. 0.46 [0.24–0.72] vs. 0.31 [0.19–0.43], both P<0.05). The receiver operating characteristic (ROC) curve showed that AGI can be used to distinguish FT1DM and T1ADM patients with HbA1c<8.7%. Diagnosing FT1DM based on AGI≤0.3 only can help narrow down suspected FT1DM by up to 26.87%. If we diagnosed FT1DM when AGI was ≤0.3 and HbA1c was ≤7.0%, the success rate further increased to 86.57%, among which 85.00% of FT1DM and 87.23% of T1ADM patients were successfully identified. Therefore, using the combination criteria of AGI and HbA1c would improve the differential diagnosis efficacy by 61.11% compared with the AGI criterion only. Conclusion. AGI can help facilitate the early differential diagnosis of FT1DM and T1ADM when HbA1c<8.7%, with an optimal cut-off point of 0.3.